A consistent pattern of minor immunodeficiency and subtle enteropathy in children with multiple food allergy - Gomes, L. (2004)
J Pediatr Gastroenterol Nutr. 2004 Jul;39(1):101-2. A consistent pattern of minor immunodeficiency and subtle enteropathy in children with multiple food allergy. Gomes L, Dias JA. Hospital Santo António, Porto, Portugal. PMID: 15187791 [PubMed - indexed for MEDLINE]